Detection and Molecular Characterization of Porcine Parvovirus 7 in Eastern Inner Mongolia Autonomous Region, China - Wen, Shubo; Song, Yang; Lv, Xiangyu; Meng, Xiaogang; Liu, Kai; Yang, Jingfeng; Diao, Fengying; He, Jinfei; Huo, Xiaowei; Chen, Zeliang; Zhai, Jingbo (Frontiers in Veterinary Science, 2022)
Porcine parvoviruses (PPV) and porcine circoviruses type 2 (PCV2) are widespread in the pig population. Recently, it was suggested that PPV7 may stimulate PCV2 and PCV3 replication. The present study aimed to make detection and molecular characterization of PPV7 for the first time in eastern Inner Mongolia Autonomous Region, China. Twenty-seven of ninety-four samples (28.72%) and five in eight pig farms were PPV7 positive. Further detection showed that the co-infection rate of PPV7 and PCV2 was 20.21% (19/94), and 9.59% (9/94) for PPV7 and PCV3. In addition, the positive rate of PPV7 in PCV2 positive samples was higher than that in PCV2 negative samples, supporting that PCV2 could act as a co-factor for PPV7 infection. In total, four PPV7 strains were sequenced and designated as NM-14, NM-19, NM-4, and NM-40. The amplified genome sequence of NM-14 and NM-40 were 3,999nt in length, while NM-19 and NM-4 were 3,996nt with a three nucleotides deletion at 3,097–3,099, resulting in an amino acid deletion in the Cap protein. Phylogenetic analysis based on the capsid amino acid (aa) sequences showed that 52 PPV7 strains were divided into two clades, and the four PPV7 strains in this study were all clustered in clade 1. The genome and capsid amino acid sequence of the four PPV7 strains identified in this study shared 80.0–96.9% and 85.9–100% similarity with that of 48 PPV7 reference strains selected in NCBI. Simplot analysis revealed that NM-19 and NM-4 strains were probably produced by recombination of two PPV7 strains from China. The amino acid sequence alignment analysis of capsid revealed that the four PPV7 strains detected in Inner Mongolia had multiple amino acid mutations in the 6 B cell linear epitopes compared with the reference strains, suggesting that the four PPV7 strains may have different characteristics in receptor binding and immunogenicity. In summary, this paper reported the PPV7 infection and molecular characterization in the eastern of Inner Mongolia Autonomous Region for the first time, which is helpful to understand the molecular epidemic characteristics of PPV7.